2019
DOI: 10.3390/electronics8040405
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparative Analysis of Impedance-Source Networks for DC and AC Application

Abstract: This paper presents a comprehensive analytical comparison of the impedance-source-based dc-dc and dc-ac converters in terms of the passive component count and size, semiconductor stress, and range of input voltage variation. The conventional solution with a boost converter was considered as a reference value. The main criterion of the comprehensive comparison was the energy stored in the passive elements, which was considered both under a constant and predefined high frequency current ripple in the inductors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Figure 2 shows a comparative diagram for the estimation of the pros and cons of the interleaving approach for the qZSI. The method of comparison is described in several papers [18,21]; here, we used a modified version. Five parameters were used for comparison: weighted summarized losses of transistors T L , weighted summarized losses of diodes D L , weighted inductors volume Vol L , weighted capacitors volume Vol C and the weighted cost of semiconductors.…”
Section: Component Selection and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows a comparative diagram for the estimation of the pros and cons of the interleaving approach for the qZSI. The method of comparison is described in several papers [18,21]; here, we used a modified version. Five parameters were used for comparison: weighted summarized losses of transistors T L , weighted summarized losses of diodes D L , weighted inductors volume Vol L , weighted capacitors volume Vol C and the weighted cost of semiconductors.…”
Section: Component Selection and Comparisonmentioning
confidence: 99%
“…At the same time, several papers [18][19][20][21] have disclosed the problems of Z-source networks. In particular, passive component size and overall efficiency are considered a bottleneck in Z-sourcebased solutions.…”
Section: Introductionmentioning
confidence: 99%
“…New solutions are required to design an inverter with wide input voltage regulation along with high-power density and acceptable efficiency. For almost a decade, the impedance-source converters have attracted attention of the researchers [17][18][19][20][21][22]. But only a few attempts of industrial design can be found [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed modulation method is validated though simulation and experimental results. A comprehensive comparative analysis of impedance-source based DC-DC and DC-AC converters regarding passive component count and size, range of input voltage variation, and semiconductor stress is proposed in [18]. The authors analyzed the main impedance-source converters with or without inductor coupling and with or without a transformer; useing simulations and experiments to validate this.…”
Section: Introductionmentioning
confidence: 99%